Analisis Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility (CSR) Sebagai Variabel Moderasi (Pada Perusahaan Perbankan Yang Terdaftar Di BEI 2020 – 2022) - Sentosa, Dimas Rio; Tambunan, Parulian (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Currently, economic realities in Indonesia have resulted in intense competition among business people. Every company has technological advances that can help disseminate financial information to investors. Business value is important to change investor attitudes and provide a convincing reason to invest. so that companies in Indonesia are increasingly focusing on the Indonesian Stock Exchange, offering the best service, and ensuring fair compensation for employees. The growth of the banking industry is very important to meet society's needs and has a significant influence on other industries. This research was conducted to find out how profitability and dividend policy can influence company value with corporate social responsibility as a moderating variable in banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample method uses purposive sampling. The samples selected in this research were 10 banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is quantitative research and uses panel data regression. The research results show that profitability has no significant effect on company value, dividend policy has a significant effect on company value, corporate social responsibility cannot moderate the effect of profitability on firm value, however corporate social responsibility can moderate the influence of dividend policy on company value.